2019
DOI: 10.1542/peds.2018-2800
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent and Young Adult Cancer Patients’ Experiences With Treatment Decision-making

Abstract: BACKGROUND: Adolescents and young adults (AYAs) with cancer generally want to engage in decision-making but are not always able to do so. We evaluated cancer treatment decision-making among AYAs, including decisional engagement and regret. METHODS: We surveyed 203 AYA patients with cancer aged 15 to 29 (response rate 74%) treated at a large academic center and their oncologists. Patients were approached within 6 weeks of diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
114
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(123 citation statements)
references
References 35 publications
4
114
0
2
Order By: Relevance
“…AYAs reported that a core component of decision making is their desire for oncologists to make time to understand their hopes, fears, and priorities—their personal definitions of living well. When this happens, oncologist‐patient relationships develop that enable AYAs to collaborate in the coproduction of their health through the joint creation of their health care plan 12 . AYAs also reported finding benefit from considering various options in the context of their personal goals and priorities 12 …”
Section: Introductionmentioning
confidence: 99%
“…AYAs reported that a core component of decision making is their desire for oncologists to make time to understand their hopes, fears, and priorities—their personal definitions of living well. When this happens, oncologist‐patient relationships develop that enable AYAs to collaborate in the coproduction of their health through the joint creation of their health care plan 12 . AYAs also reported finding benefit from considering various options in the context of their personal goals and priorities 12 …”
Section: Introductionmentioning
confidence: 99%
“…AYAs and PTPs in this pilot indicated a desire to have a more active role in decision making when compared to AYAs newly diagnosed with cancer 13 . This may be due to improved understanding of the nuances of the disease course and potential treatments that come with being on therapy for a longer time; AYAs in this study had a median time on therapy of 17 months.…”
Section: Discussionmentioning
confidence: 84%
“…[9][10][11][12] A recent study indicated most AYAs with newly diagnosed cancer preferred to make a decision in collaboration with their oncologist, while 20% wanted to hold the primary role in decision making. 13 When considering enrollment on a Phase 1 trial, 85% of AYAs report being the final decision maker. 14 Despite these findings, we are aware of no prior studies examining AYA preferences for treatment-related factors in advanced cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Despite valuing parenthood, 12 many adolescents do not bank sperm prior to initiation of gonadotoxic cancer treatment. 11,13 In the cancer setting, adolescents and young adults (AYA) often make medical decisions collaboratively with a parent, 14,15 and previous research indicates that parents have a critical role in AYAs' decision to bank sperm. [16][17][18] AYAs whose parents recommend sperm banking are over 12 times more likely to make a collection attempt relative to those whose parents do not.…”
mentioning
confidence: 99%